Penegakan Hukum Terhadap Magic Mushroom - I Gusti Ngurah Yudha Prasetia; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2021)
Mushrooms that grow in animal waste or commonly called magic mushrooms / psilocybin mushrooms are mushrooms that contain an active substance called psilocybin which can create high levels of psychological hallucinatory effects when consumed. not many know that this mushroom is a narcotic class. From the background above, the formulation of the problem is 1. How is the legal arrangement regarding Magic Mushroom? 2. What are the legal consequences of increasing and enforcing the law on Magic Mushroom?. The method used is normative legal research. The results of the discussion on the regulation of Magic Mushroom are regulated in Law no. 35 of 2009 on Narcotics and Health Law no. 36 of 2009. Regarding the legal consequences of increasing Magic Mushrooms in Indonesia, it has a bad impact on individuals, families, nations and countries, therefore law enforcement is taken by the government by taking preventive measures regarding the dangers of consuming magic mushrooms and applying criminal sanctions for users and dealers. The author suggests that the government conducts socialization and counseling to the community, especially those who are still lacking technology about the dangers of Magic Mushrooms for consumption.